Public investment to reverse Dutch disease: the case of Chad - Levy, Stephanie (International Food Policy Research Institute, 2006)
This paper studies the relevance of agricultural policies for avoiding Dutch Disease, which affects many less developed countries experiencing a resource boom. Using a computable general equilibrium model calibrated for Chad, we study the impact of using this country’s annual oil revenue for public investment, particularly in the development of road and irrigation infrastructure. Our model takes into account the integration of markets and migration processes. We find that improving water access would reduce Chad’s dependence on food aid and entail a substantial improvement in rural household welfare.